Clinical significance of programmed death 1 ligand-1 (CD274/PD-L1) and intra-tumoral CD8+ T-cell infiltration in stage II–III colorectal cancer - Chih-Yang Huang (Nature Portfolio, 2018)
Abstract Programmed cell death-1 (PDCD1/PD-1) and its ligand programmed cell death 1 ligand 1 (CD274/PD-L1) have been reported to suppress anti-tumor T cell-mediated immune responses. However, the clinical significance of CD274 in colorectal cancer were still elusive. We aim to clarify the relationships between CD8+ intratumor-infiltrating lymphocytes (TILs) and CD274 as well as their prognostic values in stage II-III colon carcinoma. Tumor differentiation, perineural invasion (PNI), pN stage and DNA mismatch repair (MMR)-deficient were clearly correlated with CD8+ TILs counts within the tumor microenvironment (p < 0.0001). Furthermore, tumor differentiation and PNI were suggestively correlated with tumor CD274 expression (p = 0.02 and p = 0.0195). Tumor CD274 level was significantly correlated with higher CD8+ TILs (p < 0.0001) but was not associated with MMR-deficient status (p = 0.14). High tumor CD274 expression [hazard ratio (HR) = 2.16, 95% CI = 1.63–2.86, p < 0.0001] and CD8+ TILs [HR = 1.51, 95% CI = 1.19–1.91, p = 0.0007] were associated with improved disease-free survival and overall survival. Additionally, the subgroup of patients who had a high CD8+ TILs/tumor CD274 have better survival outcomes compared with other subgroups (71% vs 53%; p < 0.0001). Therefore, the CD8+ TILs counts and tumor CD274 may be prognostic factors to predict survival and therapeutic responses in stage II–III colon carcinoma patients.